Risk Factors and Incidence of Epilepsy after Severe Traumatic Brain Injury. Issue 4 (3rd August 2022) - Pease, Matthew; Gonzalez‐Martinez, Jorge; Puccio, Ava; Nwachuku, Enyinna; Castellano, James F.; Okonkwo, David O.; Elmer, Jonathan
Abstract : We determined the incidence of post‐traumatic epilepsy after severe traumatic brain injury. Of 392 patients surviving to discharge, cumulative incidence of post‐traumatic epilepsy was 25% at 5 years and 32% at 15 years, an increase compared with historical reports. Among patients with one late seizure (>7 days post‐trauma), the risk of seizure recurrence was 62% after 1 year and 82% at 10 years. Competing hazards regression identified age, decompressive hemicraniectomy, and intracranial infection as independent predictors of post‐traumatic epilepsy. Patients with severe traumatic brain injury and a single late post‐traumatic seizure will likely require long‐term antiseizure medicines. ANN NEUROL 2022;92:663–669